Cerebral Oximetry in Cardiac Surgery - A. N. Shepelyuk; T. V Klypa; Yu. V. Nikiforov (Общая реаниматология, 2012)
Based on the data of numerous current references, the review describes different neuromonitoring methods during cardiac surgery under extracorporeal circulation. It shows that it is important and necessary to make neuromonitoring for the early diagnosis and prevention of neurological complications after cardiac surgery. Particular attention is given to cerebral oximetry; the possibilities and advantages of this technique are described. Correction of cerebral oximetric values is shown to improve survival rates and to reduce the incidence of postoperative complications. Lack of cerebral oximetry monitoring denudes a clinician of important information and possibilities to optimize patient status and to prevent potentially menacing complications, which allows one to conclude that it is necessary to use cerebral oximetry procedures within neu-romonitoring in cardiac surgery. Key words: extracorporeal circulation, cerebral oximetry, neurological dysfunction, cerebral oxygenation.